Priority quality traits for gendered sweetpotato breeding in Mozambique - Mayanja, Sarah; Tinyiro, Samuel Edgar; Ogwal, David Martin; Makunde, Godwill; Naico, Abdul; Nakitto, Mariam; Ssali, Reuben; Andrade, Maria (Frontiers in Sustainable Food Systems, 2023)
Sweetpotato breeders strive to develop varieties that address productivity challenges farmers face in sub-Saharan Africa (SSA). However, adoption of these varieties is low, partly attributed to limited attention to attributes desired by the end-users. This study sought to identify the key traits preferred by eight women processors and 426 consumers (180 male, 246 female) in Manhiça, Marracuene and Maputo districts, Mozambique. Processing diagnostics and consumer studies evaluated two local varieties (‘Lilas’, ‘N’santimuni’) and two improved varieties (‘Alisha’, ‘Irene’). Data from processors were analyzed using content analysis and summary statistics. Consumer hedonic data were analyzed using clustering and regression models, while Penalty analysis and Multiple correspondence analysis were performed for the Just-about-right and Check-all-that-apply tests respectively. Processors prioritized mealiness, sweet taste, not fibrous, good sweetpotato smell, ease of peeling, easy to cook and good appearance for the boiled root. ‘N’santimuni’ was the most preferred variety for processing. Consumers preferred ‘N’santimuni’ and ‘Lilas’ because of their high dry matter, pleasant sweetpotato smell, firmness in the hand, smoothness when eating and sweet taste. ‘Alisha’ and ‘Irene’ were the most penalized for low scores on sweetness, mealiness, and firmness. Women consumed sweetpotato more frequently than men and had better discernment of sweet taste, homogeneity and colour. Also, youth and more educated consumers disliked improved varieties more than adults and lower income consumers. Breeding programs can be enhanced by studies of biophysical and chemical parameters of sweetpotato. This will quantify and enable incorporation of quality attributes such as mealiness, firmness and sweet taste.